PD‐L1 expression and deficient mismatch repair in ductal adenocarcinoma of the prostate. Issue 8 (19th July 2019) - Lindh, Claes; Kis, Lorand; Delahunt, Brett; Samaratunga, Hemamali; Yaxley, John; Wiklund, Nils Peter; Clements, Mark; Egevad, Lars
Abstract : This study aimed to investigate the expression of programmed death receptor ligand 1 (PD‐L1) and deficient mismatch repair (dMMR) in ductal adenocarcinoma of the prostate. A tissue microarray of 32 ductal and 42 grade‐matched acinar adenocarcinomas was used. Slides were stained for PD‐L1, PD‐L2, MMR proteins, CD4 and CD8. PD‐L1 expression in tumor cells was only seen in 3% (1/34) of ductal and 5% (2/42) of acinar adenocarcinomas (p = 1.0), while PD‐L1 expression in tumor‐infiltrating immune cells was seen in 29% (10/34) of ductal and 14% (6/42) of acinar adenocarcinomas (p = 0.16). dMMR, as defined by loss of one or more of the MMR proteins, was identified in 5% (4/73) of cases, including 1 ductal and 3 acinar adenocarcinomas. There was a suggested association between infiltration of CD8+ lymphocytes and ductal subtype (p = 0.04) but not between CD4+ lymphocytes and tumor type (p = 0.28). The study shows that both dMMR and PD‐L1 expression is uncommon in tumor cells of both ductal and acinar adenocarcinoma of the prostate, while PD‐L1 expression in tumor‐infiltrating immune cells is a more common finding.